Strategies for Rot Control of Soybean Sprouts - Choi, Jae-Suk (Recent Patents on Food, Nutrition & Agriculture, 2019)
Soybean sprouts are nutrient-rich, contain plentiful proteins, vitamin C, and minerals and are packed in small numbers after production. As soybean sprouts were mass produced in a factory, the occurrence of rotting in soybean sprouts has become a serious problem. To overcome these problems, many efforts have been made to provide healthy soybean sprouts in Korea. This paper reviewed the physicochemical techniques used for supplying water with antibacterial properties and the natural antimicrobial materials developed for soybean sprout cultivation. On the basis of this review, 11 of the antimicrobial agents and/or techniques currently used originated from mineral, non-metal ions, and metal ions, 4 from antagonistic microorganisms, 7 from agents originating from animals, 31 from medicinal and herbal plants, and 11 from physicochemical agents and/or techniques. In addition, these agents and/or techniques showed potential not only for the inhibition of spoilage and rot of soybean sprouts but also for the extension of product shelf life, the enhancement of taste and aroma, the enhancement of nutrition and functional components, growth promotion, and/or the reduction of production costs. Continuous scientific innovations and improved processing technology will aid in further advancements and improvements in this area. Therefore, this study offers useful insights suggesting direction for future research and provides information on the different anti-rotting agents and/or techniques for soybean sprouts developed to date, also as discussed in various patents.
Keywords: anti-rotting agents